2005
DOI: 10.1038/sj.onc.1208934
|View full text |Cite
|
Sign up to set email alerts
|

A human cell line that maintains telomeres in the absence of telomerase and of key markers of ALT

Abstract: In human somatic cells proliferation results in telomere shortening due to the end replication problem and the absence of adequate levels of telomerase activity. The progressive loss of telomeric DNA has been associated with replicative senescence. Maintenance of telomere structure and function is, therefore, an essential requisite for cells that proliferate indefinitely. Human cells that have acquired the immortal phenotype mostly rely on telomerase to compensate for telomere shortening with cell division. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 55 publications
(74 reference statements)
4
52
0
2
Order By: Relevance
“…2C), suggesting that elongation of the shortest telomeres by telomerase may affect the recruitment of chromosome extremities to APBs. In an atypical ALT cell line derived from VA13 cells (VA13-C3-cl6), in which APBs are virtually absent (20), telomere clusters were rarely detected ( Fig. 2 A and C), as expected.…”
Section: Telomeres Are Not Randomly Distributed But Cluster Around Pmlsupporting
confidence: 83%
See 1 more Smart Citation
“…2C), suggesting that elongation of the shortest telomeres by telomerase may affect the recruitment of chromosome extremities to APBs. In an atypical ALT cell line derived from VA13 cells (VA13-C3-cl6), in which APBs are virtually absent (20), telomere clusters were rarely detected ( Fig. 2 A and C), as expected.…”
Section: Telomeres Are Not Randomly Distributed But Cluster Around Pmlsupporting
confidence: 83%
“…VA13 cells that stably express hTERT and hTR (VA13ϩtelomerase) maintain telomeres by both mechanisms, ALT and telomerase. VA13-C3-cl6 is a clonal cell line derived from VA13 that maintains telomeres by an atypical ALT pathway in the absence of APBs (20). HT1080 is a telomerasepositive human lung sarcoma cell line.…”
Section: Methodsmentioning
confidence: 99%
“…One possible explanation could be that telomerase did not completely revert the ALT pathway and/or the associated telomeric heterochromatinization, as suggested earlier (Perrem et al, 2001;Cerone et al, 2005). However, the telomeric repeat addition at short chromosome ends that we observed upon telomerase expression suggests that telomerase T-SCE does not require subtelomeric DNA hypomethylation G Tilman et al acted at the telomeres of these ALT cells.…”
Section: Discussionmentioning
confidence: 47%
“…cerevisiae strains deficient for telomerase can survive with long and heterogeneous telomeres composed of amplified telomere repeats (type II survivors) (7,8). Analogous to type II survivors, long and heterogeneous telomeres occur in almost all in vitro immortalized cell lines and tumor-derived cells lines that are telomerase-negative (9)(10)(11). Furthermore, extensive analysis of telomerase activity and telomere length from primary human tumor samples has revealed that certain telomerase-negative tumors possess long and heterogeneous telomeres, defined as alternative lengthening of telomeres (ALT) tumors (9).…”
Section: Protection Of Telomeres-2 | Telomere Maintenancementioning
confidence: 99%